The Meanings Mentioned in the Quran - objective study (Journal of the College of Education for Women, 2019)
Praise be to God, who has seen uniting the wonders of manufactures, and pronounced Pthamidh oddity Alambdoat, and swam his creation in different languages, Glory is not equal to one in the earth and the heavens, praise Him, and I bear witness that there is no god but Allah alone with no partner certificate towering branches, and I bear witness that Muhammad is His slave and Messenger sent swage Arab government balance, and clearest statement, and the highest residence and Ohllagha words, and Oovaha Zmama, he pointed the way and advised the creation, and the month of Islam, breaking idols, and showed provisions, uncle Balanaam, God separated blessings and peace upon our Prophet Muhammad and the God of the good and virtuous and his companions honorable sons and his wives and offspring in every forum and denominator.After: there is no doubt that the mention of God and his prayer is the best of what it spent times and spent a breathtaking, and the best closer by slave to his Lord Almighty, which is the key to all that is good bestowed slave in this world and the hereafter. When God slave gave this key has wanted to open his and when the bounty left the door goodness Mrtja without him, remains a troubled heart, muddle-hearted, distracting thought, much anxiety,weak vigor and the will, but if the governor of the mention of God and prayed and frequent Alljo him, his heart be reassured his penis to his Lord, and diminish the benefits and virtues and fruits precious ripe in the world and the Hereafter what is known only to God ... and that Almstaheda the light of faith, and the beholder into insight, has learned an investigation; it's not the way to collect the happiness in this world and the hereafter, and win high degrees, Neil Reza right Almighty; but Bmdaomh mentioned by the Almighty, and took heart from much luck paid tribute and veneration, and he realized that he certainly does not zakat for this heart is not goodness to him; however, that is God Almighty beloved and highly required, so there is no way to absolutely, but his knowledge of the Almighty and attendance mentioned. I found it is necessary to discuss this issue and the statement of his order and meaning in the texts of the Koran and I teach an objective study I called (the meanings mentioned in the Koran objective study), and made him after the introduction of five sections and a conclusion: First topic: the meaning of the language of male and idiomatically. The second topic: the male species, and be rewarded for it from him. The third topic: the benefits mentioned in this world and the hereafter. The fourth topic: the meanings mentioned in the Koranic texts. The fifth topic: the remembrance of Allah Almighty and good relates.(We ask God Almighty, Lord of the Great Throne, to guide us to what he loves and is pleased، And that makes this work-to-face Karim)